Acesso ao primeiro emprego: barreiras e facilitadores na percepção de jovens de 14 a 24 anos - Luciana Ferreira Gomes (2021)
The aim of this study was to identify, according to the perception of young people aged 14 to 24, barriers and facilitators for accessing their first formal job. Quantitative in nature, the present study used an online questionnaire for data collection, available from March to June 2021 on the Google Forms platform, disclosed on social networks and in companies that work in placing young people in their first formal job. For data treatment and analysis, each question was classified according to the dimension to which it fit, that is, individual, contextual or macro-structural, as well as the facilitator or barrier situation. In addition, the 5-point Likert scale was adapted for dichotomous outcomes, that is, agree and disagree, grouping the responses of agreement and disagreement into distinct groups. The sample consisted of 107 respondents, distributed through out Brazil. From the statistical analysis of the results obtained, it can be seen that the individual dimension is the one that stands out among those analyzed and comprises, according to the perception of the young people surveyed, both the main barrier to accessing a first job – low level of education – and the most important facilitator – on-the-job training course. In the contextual dimension, family support is highlighted as a facilitator and the lack of money for public transport as a barrier. In the macro-structural dimension, the country's economic situation constitutes an important barrier to entering a first job and access to the internet, a facilitator. This study allowed us to conclude that the young people surveyed attribute to the individual the success or failure in obtaining their first formal job, recognizing the individual dimension as the one with the greatest impact on the studied outcome, in line with the individualism spread by the neoliberal capitalist ideology.